PEMBUATAN MINUMAN JAMU HERBAL GUNA MENINGKATKAN DAYA TAHAN TUBUH SERTA PENDISTRIBUSIAN KEPADA MASYARAKAT KELURAHAN SAGO DI ERA NEW NORMAL - Zufriady,; Adhitya Hidayah Ramadhan,; Fitri Andini,; Muhammad Fathir Ar Rasyid,; Maharani, Maharani; Dzahwa Lailatul Najmi,; Rara Salfa Arsenda,; Diah Aisyah Pramesti,; Affifah Zahra Al Ghifari,; Mutia Saputri,; Raindy Harvian, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The "Real Work Lecture" service activity organized by Riau University students has launched and carried out work programs in the new normal period. One of the work programs that have been implemented is the manufacture and distribution of healthy herbal ginger drinks to the community. The implementation of the program is due to seeing that in the past the government's decision on the use of masks has been revoked. Students considered that it would be very important to continue to carry out work programs on health support aspects in the community. The work program is also planned and implemented considering that the community in the service location is also close to access to the city center and economic center areas. This results in the assumption that the community works closely with physical contact and is likely to be a vector of disease. The results of these activities are in the form of healthy herbal ginger drink products that are distributed to the community.